Continuous Spinal Anesthesia following Inadvertent Dural Puncture during Epidural Placement for an Emergency Laparotomy. (8th March 2021) - Emyedu, Andrew; Kyoheirwe, Bernadette; Atumanya, Patience
Abstract : Summary . Emergency exploratory laparotomy conducted under continuous spinal anesthesia using a standard epidural set following an accidental dural puncture. Background and Objectives . Continuous spinal anesthesia is one of the least utilized regional anesthesia techniques globally. It could be an alternative anesthesia technique for abdominal and lower limb surgeries following an accidental dural puncture. The aim of this report was to describe a case in which continuous spinal anesthesia was successfully conducted for emergency exploratory laparotomy following an accidental dural puncture during epidural placement. Case Report . A 38-year-old male presented to our accident and emergency unit with a one-day history of colicky abdominal pain associated with constipation, abdominal distension, and vomiting. He was diagnosed with intestinal obstruction and underwent an emergency exploratory laparotomy under continuous spinal anesthesia using a standard epidural set following an accidental dural puncture. Conclusion . This case demonstrates that in case of an accidental dural puncture during epidural placement, the catheter can be advanced into the intrathecal space and continuous spinal anesthesia conducted for abdominal surgeries using a standard epidural catheter.